ANALYSIS OF THE PSYCHOSOCIAL DEVELOPMENT OF STUDENTS IN THE FIRST YEAR OF ELEMENTARY EDUCATION AT A SCHOOL IN THE MUNICIPALITY OF VOTUPORANGA-SP (International Seven Journal of Health Research, 2025)
It is essential to enable children to learn to name and express their emotions correctly so that they can reach the peak of their socio-emotional development in the future. Furthermore, it is observed that children demonstrate good levels of empathy and recognition of primary emotions, such as joy, sadness and anger. Despite this, in more complex emotional contexts, children need help and support so that they can understand and express their feelings appropriately. Unmonitored exposure to screens causes a delay in interpersonal interrelationships and, therefore, the learning of socio-emotional skills. Our results revealed that some children demonstrated sadness and frustration when they were removed from screens. For this reason, in an increasingly digital world, it is crucial that families and educators establish healthy limits for the use of technology, ensuring that they have time and space for experiences that foster adequate emotional and social development using other resources. The results highlight the importance of continually supporting the development of socio-emotional skills, in order to build a solid foundation for the improvement of essential skills such as self-control, empathy and conflict resolution, which are fundamental for adequate social and emotional development.